(AL-TAHRIRAT AL-MANAWIYA ON AL-RISALAH AL-DALAJIYAH) BY SHEIKH TAJ AL-DIN AL-MANAWI, IN THE SCIENCE OF HADITH - Ahmed, naaman; Jameel, Izadeen (Humanities Journal of University of Zakho, 2026)
(Al-Tahrirat Al-Manawiya on Al-Risalah Al-Dalajiyah) by Sheikh Taj al-Din al-Manawi, in the Science of Hadith. This message is an investigative study in the science of hadith and the terminology related to it. It is entitled (Altahrirat Almanawiah on Al-Risalah Al-Daljiyyah), by its author Sheikh Taj al-Din Ibn al-Manawi - may God Almighty have mercy on him - and this is a singular and unique individualistic script, which is an explanation on (Al-Risalah Al-Daljiyah) by Sheikh Muhammad bin Muhammad Al-Dalji - may God Almighty have mercy on him - and Sheikh Taj Al-Din explained it in a detailed and comprehensive manner, in a way that gives the message its due, explains the solution to its problems, and makes it easy to understand its objectives. The study aims to explain terms that are related to the science of hadith, and that are used by specialized scholars in the science of hadith. It also aims to include hadiths related to these terms to clarify them for beginners and those who are unfamiliar with their meanings. All of this is done carefully to include the differences of the skilled scholars and their statements on this subject, and interestingly to clarify their responses to each other on some issues. The Sheikh - may God Almighty have mercy on him -, he relied on reliable and trustworthy sources and references of the modern scholars in explaining the Daljiyah message, such as: Ibn al-Salah, Ibn Hajar, and his father Sheikh Abdul-Ra’uf al-Manawi - may God Almighty have mercy on them - and other imams of the science of hadith. He did not stop at this point, but rather the Sheikh - may God Almighty have mercy on him - clarified in his explanation the opinions of the scholars on judging on some hadiths, such as authenticity, weakness, and other levels of hadith, and a statement of the principles and rules of correcting and criticizing men. Also, the Sheikh - may God Almighty have mercy on him - added valuable notes in some of the chapters, which have great benefits. I wanted to verify this manuscript, God Almighty willing, to enrich the Islamic library with it in terms of knowledge of the science of hadith.